Fluctuation induces conductivity and microstructural studies in Y-123: Effect of CaO inclusion - Yap, Siew Hong; Awang Kechik, Mohd Mustafa; Mohd Shariff, Khairul Khaizi; Baqiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Mohd Zaid, Mohd Hafiz; Yaakob, Yazid; Abdul Karim, Mohd Khalis; Humaidi, Syahrul; Shaari, Abdul Halim; et al. (Elsevier, 2024)
This study explored the impact of CaO as effective fine pinning centres on the interactions among thermodynamic fluctuations of superconducting parameters during the superconducting transitions in the Y-123 (YBa2Cu3O7-δ) matrix system. The investigation involved introducing varying concentrations (0.0100 wt% ≤ × ≤ 0.6000 wt%) of CaO into the Y-123 matrix through a green approach thermal treatment method annealed in an oxygen flow. TGA-DTA analysis revealed that the thermal stability of CaO exceeded that of the Y-123 matrix system. In XRD results, all specimens crystallized into orthorhombic Y-123 as the main phase, accompanied by non-superconducting phases such as Y-211 and BaCuO2, contributing to the enhancement of superconducting parameters. These inclusions of CaO induced distinct trends in grain degradation, spiral grain growth, and the appearance of homogeneous Y-123 nano-entities within the Y-123 matrix system. DC resistivity measurements investigating thermal fluctuation conductivity showed reductions in transition temperature widths (ΔTc and ΔTcMF1-offset) reaching an optimal concentration of CaO inclusion at 0.0375 wt%. Additionally, intra-granular current density at 0 K (Jc(0)) experienced significant improvements at lower concentrations, peaking at 0.0375 wt% at 11.0 ×106 A/m2. The incorporation of CaO at 0.0375 wt% proved optimal for achieving finely scaled lattice defects in intergranular and intragranular coupling, serving as effective pinning centres. This dominance in the 3D regime of thermal fluctuation reduced flux motion and improved Jc(0). The study concluded that the deficient inclusion of CaO led to the well-dispersed formation of nano-sized Y-123 particles, enhancing the superconducting parameters.